The Effect of Organizational Commitment on Employee Retention Mediated By Job Satisfaction (A Study At PT. BPR Tri Darma Putri Klungkung) - Ni Luh Sri Madewi; Ni Wayan Mujiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee retention is a crucial aspect of human resource management, reflecting an organization's ability to retain its workforce over the long term. This study aims to analyze the effect of organizational commitment on employee retention, with job satisfaction as a mediating variable. The study was conducted at PT. BPR Tri Darma Putri Klungkung, involving a total of 57 employees as respondents. A quantitative associative approach was employed, and data were collected using a structured questionnaire. Data analysis was carried out using Partial Least Squares (PLS) based on Structural Equation Modeling (SEM). The results reveal that organizational commitment has a significant positive effect on employee retention. Additionally, organizational commitment significantly affects job satisfaction, and job satisfaction, in turn, has a significant positive influence on employee retention. Furthermore, job satisfaction partially and complementarily mediates the relationship between organizational commitment and employee retention at PT. BPR Tri Darma Putri Klungkung. This study reinforces social exchange theory and offers practical implications for company management to enhance employee retention through strengthening commitment and job satisfaction.